Elevated emotion reactivity and emotion regulation in individuals at clinical high risk for developing psychosis and those diagnosed with a psychotic disorder. Issue 7 (15th September 2021) - Vines, Leah; Bridgwater, Miranda; Bachman, Peter; Hayes, Rebecca; Catalano, Sabrina; Jalbrzikowski, Maria
Abstract: Aims: Disrupted affective processes are core features of psychosis; yet emotion reactivity and emotion regulation impairments have not been fully characterized in individuals at clinical high‐risk for developing psychosis (CHR) or adolescents diagnosed with a psychotic disorder (AOP). Characterizing these impairments may provide a fuller understanding of factors contributing to psychosis risk and psychosis onset. Using cross‐sectional and longitudinal data, we evaluated (1) group‐level effects of emotion reactivity and regulation, (2) stability of group‐level effects over time and age, (3) relationships between emotion reactivity and regulation, and (4) associations between these measures and psychosocial functioning and clinical symptomatology. Methods: Eighty‐seven participants (CHR = 32, TD = 42, AOP = 13; 12–25 years, 1–5 visits) completed the Emotion Reactivity Scale, Difficulties in Emotion Regulation Scale, and Emotion Regulation Questionnaire. We assessed psychotic symptoms with the Structured Interview for Prodromal Syndromes and measured real‐world functioning with the Global Functioning: Social and Role Scales. We used analysis of variance to assess Aim 1 and linear mixed models to address Aims 2–4. Results: CHR and AOP endorsed experiencing heightened levels of emotion reactivity and greater difficulty utilizing emotion regulation strategies compared to TD. These impairments were stable across time and adolescent development. Greater levels of emotion reactivity were associated with greater emotion regulation impairments. Greater impairments in emotion regulation were associated with lower social functioning and greater negative symptom severity. Conclusion: Therapeutic interventions designed to reduce emotion reactivity and improve one's ability to utilize emotion regulation strategies may be effective in reducing clinical symptomatology and improving real‐world functioning in CHR and AOP.